Life-Writing and the Theme of Cultural Decline in Valeriano's De Litteratorum Infelicitate - Gouwens, Kenneth (The sixteenth century journal, 1996)
Although often described as an account of the destruction of Italian humanism by the Sack of Rome, Valeriano's dialogue, De litteratorum infelicitate, actually affirms continuity, both by redefining the republic of letters to have greater independence from Rome, and by forging a consistent identity over time for Valeriano himself. Minibiographies spanning several decades deploy the sufferings of learned contemporaries as exempla of the perennial condition of scholars, victims of fortune. Despite its prosopographical form, Valeriano uses the dialogue to articulate a coherent narrative of his own career. Situating his move from Rome to Belluno in the context of the de-centering of Italian humanistic culture after 1527, he establishes continuities-both individual and collective-that later readers of his dialogue have, ironically, used it to deny.